MARKET BASKET ANALYSIS OF ADMINISTRATIVE PATTERNS DATA OF CONSUMER PURCHASES USING DATA MINING TECHNOLOGY - Samboteng, Lukman; Rulinawaty, Rulinawaty; Kasmad, M.Rachmat; Basit, Mutmainnah; Rahim, Robbi (Journal of Applied Engineering Science, 2022)
Food is the ingredient that enables people to grow, develop, and achieve. For this reason, food quality and types of food must be considered so that they are safe for consumption and managed. Some plant-based foodstuffs are often processed and consumed by the community, even the most needed in food processing. In this case, the research was carried out using data mining with market basket analysis algorithms to obtain very valuable information to decide the inventory of the type of material needed. Market Based Analysis method is used to analyze all data and create patterns for each data. One method of Market Based Analysis in question is the association rule with a priori algorithm. This algorithm produces sales transactions with strong associations between items in the transaction which are used as sales recommendations that help users (owners) get recommendations when users see details of the itemset purchased. From the results of the trials in this study, it was found that the greater the minimum support (minsup) and minimum confidence (minconf), the less time it takes to produce recommendations and the fewer recommendations are given, but the recommendations given come from transactions that often appear.
Keywords: apriori algorithms, transaction data, data mining, associations, consumer patterns